(untitled) (Terr@ Plural, 2022)
Fires have taken a central role in the discussions on environmental conservation in Brazil and worldwide. In this study, we investigated the temporal evolution of soil cover and the restoration of vegetation in a burned area (BA) and another unburned area (UBA) in a Cerrado stricto sensu, using aerial images and the ImageJ® software. Soil cover changed little over time and there was no difference between the areas regarding restoration of vegetation. Otherwise, the ImageJ® software proved useful in evaluating the evolution of soil cover and, due to its simplicity and free access, it can be used in the processing of individual images for the calculation of exposed soil area.